Synthesis, Spectroscopic Characterization and Antibactrial Activities of Co(II) Complex of Ofloxacin Drug Mixed with Ascorbic Acid as a Secondary Ligand - Onyenze, Ugochukwu; Ifeanyi Edozie, Otuokere (BioScientific Review, 2021)
Ofloxacin is a quinolone antibiotic. It is considered an efficient antibacterial drug with a broad spectrum of activity against anaerobic and aerobic bacteria. Moreover, it shows strong antibacterial activity in vitro against many bacteria species by inhibiting their DNA-gyrase. In this study, the synthesis, physicochemical and spectroscopic characterization of Cobalt (II) metal complex, with ofloxacin as the primary ligand and ascorbic acid as the secondary ligand were achieved. The complex was prepared by using the reflux method for four hours in methanol. The complex, with the molecular formula [Co(Ofl)(Asc)], was characterized by its color, solubility, melting point, FTIR, UV/Visible, 1H NMR, and 13C NMR spectroscopy. The color and the melting point suggested that complexation occurred. The Fourier Transform Infrared data for both the primary ligand (Ofl) and the secondary ligand (Asc) acted as tridentate ligands. Ofl coordinated with the Co(II) metal ion via the two carbonyl oxygen atoms and the oxygen atom of the hydroxyl group, whereas Asc coordinated with the metal through the carbonyl and enolic C-2 and C-3 hydroxyl groups. Electronic data suggested octahedral geometry for the complex. The ligands and the novel Co (II) complex were tested for in vitro antibacterial activity against gram-negative and gram-positive bacterial species using the filter paper disc agar diffusion method. Significant antibacterial activities were observed against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Candida albicans for the complex as compared to the ligands. This research will aid in the development of more potent drugs that are resistant to organisms. Keywords: antibacterial activity, ascorbic acid, cobalt (II), mixed ligand, ofloxacin. Copyright (c) The Authors